Novel wasp toxin discriminates between neuronal and cardiac sodium channels - Kinoshita, E.; Maejima, H.; Yamaoka, K.; Konno, K.; Kawai, N.; Shimizu, E.; Yokote, S.; Nakayama, H.; Seyama, I (Amer Soc Pharmacology Experimental Therapeutics, 2001)
Pompilidotoxins (PMTXs), derived from the venom of solitary wasp has been known to facilitate synaptic transmission in the lobster neuromuscular junction, and a recent further study from rat trigeminal neurons revealed that the toxin slows Na+ channel inactivation without modifying activation process. Here we report that beta -PMTX modifies rat brain type II Na+ channel alpha -subunit (rBII) expressed in human embryonic kidney cells but fails to act on the rat heart alpha -subunit (rH1) at similar concentrations. We constructed a series of chimeric mutants of rBII and rH1 Na+ channels and compared modification of the steady-state Na+ currents by beta -PMTX. We found that a difference in a single amino acid between Glu-1616 in rBII and Gln-1615 in rH1 at the extracellular loop of D4S3-S4 is crucial for the action of beta -PMTX. PMTXs, which are small peptides with 13 amino acids, would be a potential tool for exploring a new functional moiety of Na+ channels.